Public speaking and presentations demystified - Templeton, Melody (New York : McGraw-Hill, 2010)
The book guides one through the art of public speaking and presentations. It provides insight into how to brainstorm your topic, analyse your potential audience and the message you 'll want them to hear, and prepare for the actual day. it offers tips on beating performance anxiety and overcoming stage fright.
"A self-teaching guide"--Cover.
Includes bibliographical references and index.
rua 15/05/13
Loans
Keywords: Public speaking; Oral communication; Presentations